Analisis pengaruh kompetensi kepribadian dan kompetensi sosial guru terhadap kecerdasan emosional siswa - Hanif Af Idatulathifah; Syamsudin Syamsudin (At Turots: Jurnal Pendidikan Islam, 2023)
This research aims to analyze the impact of ISMUBA (Al-Islam, Kemuhammadiyahan, and Arabic Language) teachers' personality competence and social competence on students' emotional intelligence at SMP MBS Al-Manar from the students' perspectives. The study utilized a quantitative approach, involving a sample of 52 students selected through a census technique. The data were analyzed using simple linear regression with SPSS 22. The findings indicate that ISMUBA teachers' personality competence falls within the low category, while their social competence is categorized as medium. Additionally, the results demonstrate that students' emotional intelligence is in the low category. The simultaneous hypothesis test reveals a positive and significant relationship between ISMUBA teachers' personality competence and social competence, and students' emotional intelligence. Partially, the research identifies a positive and significant impact of ISMUBA teachers' personality competence on students' emotional intelligence. Moreover, there is a positive and significant effect of ISMUBA teachers' social competence on students' emotional intelligence